2019
DOI: 10.1042/cs20190672
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS-induced lysosomal dysfunction impairs autophagic flux and contributes to M1 macrophage polarization in a diabetic condition

Abstract: Macrophage polarization toward the M1 phenotype and its subsequent inflammatory response have been implicated in the progression of diabetic complications. Despite adverse consequences of autophagy impairment on macrophage inflammation, the regulation of macrophage autophagy under hyperglycemic conditions is incompletely understood. Here, we report that the autophagy-lysosome system and mitochondrial function are impaired in streptozotocin (STZ)-induced diabetic mice and high glucose (HG)-stimulated RAW 264.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Moreover, lipofuscin accumulation leads to a reduced turnover of damaged mitochondria, which results in an increase in reactive oxygen species. In turn, the oxidative stress further impedes autophagy via the additional impairment of lysosomal function [128][129][130][131][132].…”
Section: Age-related Lipofuscin Accumulation In Lysosomes Reduces Thementioning
confidence: 99%
“…Moreover, lipofuscin accumulation leads to a reduced turnover of damaged mitochondria, which results in an increase in reactive oxygen species. In turn, the oxidative stress further impedes autophagy via the additional impairment of lysosomal function [128][129][130][131][132].…”
Section: Age-related Lipofuscin Accumulation In Lysosomes Reduces Thementioning
confidence: 99%
“…The autophagic lysosomal pathway is an important pathway for intracellular protein degradation, and the cascade signals sent by lysosomes will lead to changes in autophagy flux in physiological and pathological processes. It has been shown that the polarisation of macrophages into the M1 phenotype and its subsequent inflammatory response are related to the progression of diabetic complications 26 . Mitochondrial reactive oxygen species play a key role in promoting the differentiation of macrophages into the inflammatory phenotype by damaging the autophagosomal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the polarisation of macrophages into the M1 phenotype and its subsequent inflammatory response are related to the progression of diabetic complications. 26 Mitochondrial reactive oxygen species play a key role in promoting the differentiation of macrophages into the inflammatory phenotype by damaging the autophagosomal pathway. In peripheral vascular complications of diabetes, glucose-induced apoptosis is involved in autophagosome formation through the AMPK/RAPTOR/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When secreted, these cytokines attract other mononuclear/MФ cells, neutrophils, as well as adaptive immune subsets (T and B lymphocytes, natural killer cells). Activation of TLR4 and autophagy pathways also led to the generation of ROS and NO as mediators of the pro-inflammatory potential in M1 MФs [117,118]. Indeed, MONPs increased ROS and NO levels in MФs [69].…”
Section: Functional Outcome Of Nanoparticle-macrophage Interactionsmentioning
confidence: 99%